1990
DOI: 10.1159/000461208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Platelet Activation and Membrane Glycoprotein lb and IIb-IIIa Expression after Filtration through Three Different Leukocyte Removal Filters

Abstract: We evaluated three filters used for leukocyte removal from platelet concentrates: Imugard IG 500, Pall PL100 and Sepacell PL-10A. Filter performance, platelet activation and expression of membrane glycoproteins lb and Ilb-IIIa were evaluated. Imugard, Pall and Sepacell showed median postfiltration in vitro platelet recoveries of 88, 84 and 80%, and total residual leukocyte counts of 16.1, 7.5 and 0.6 x 10^6/pool of 8 platelet concentrates, respectively. Mean platelet volume was reduced after filtration with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

1992
1992
1994
1994

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…In this study we did not observe any signif icant difference in filtered platelets mean size compared to controls. These data differ from the results of other studies performed in our and other laboratories [5,15] on platelets suspended in plasma. The reason for this differ ence may be related to the synthetic medium used for BCPC storage in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this study we did not observe any signif icant difference in filtered platelets mean size compared to controls. These data differ from the results of other studies performed in our and other laboratories [5,15] on platelets suspended in plasma. The reason for this differ ence may be related to the synthetic medium used for BCPC storage in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study we evaluated platelet in vitro viability, metabolism and activation during 15-day storage of filtered and control BCPC. In previous experi ments [15], we demonstrated that filtration procedures do not induce significant platelet activation or modifications reports demonstrating an increase of platelet-bound fibri nogen during storage; this two-step process needs a con version of membrane Ilb-IIIa complexes into functional fibrinogen receptors before ligand binding to the exposed receptors. The 9F9 antibody used in this study is known to bind to platelet-bound fibrinogen and not to fibrinogen in solution, and was previously used [24] to evaluate the extent of platelet activation.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations